The C57BL/6N mouse substrain is a viable model of elastase-induced abdominal aortic aneurysm - Wei, Panpan; Li, Kexin; Li, Meng; Liu, Haole; Xia, Congcong; Chen, Yajie; Zhao, Sihai; Li, Yankui (Frontiers in Cardiovascular Medicine, 2024)
Aim: Compared with the C57BL/6N substrain, the C57BL/6J substrain is more susceptible to the angiotensin II (Ang II)-induced development of dissected abdominal aortic aneurysms (AAAs). The aim of this study was to elucidate whether the widely used C57BL/6N mouse substrain is as susceptible as the C57BL/6J mouse substrain to porcine pancreatic elastase (PPE) infusion-induced experimental nondissected AAA development.Method: Experimental nondissected AAAs were induced in C57BL/6J and C57BL/6N mice via transient aortic luminal infusion of PPE. On Day 0 (baseline) and Day 14 after PPE infusion, the abdominal aortic diameter was directly measured. Aortic aneurysmal segment samples were collected, and histopathological analysis was performed.Results: On Day 14 after PPE infusion, aortic diameters were significantly increased in both mouse substrains (from approximately 0.51 to 1.